2014
DOI: 10.1364/ol.39.002703
|View full text |Cite
|
Sign up to set email alerts
|

Virtual source of a Pearcey beam

Abstract: A virtual source that yields a family of a Pearcey wave is demonstrated. A closed-form expression is derived for the Pearcey wave that simplifies to the paraxial Pearcey beam (PB) in the appropriate limit. From the perturbative series representation of a complex-source-point spherical wave, an infinite series nonparaxial correction expression for a PB is obtained. The infinite series expression of a PB can give accuracy up to any order of the diffraction angle. By applying the integral representation of the Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 83 publications
(42 citation statements)
references
References 26 publications
0
42
0
Order By: Relevance
“…[12]. Let us apply an inverse Fourier transform to it, then we add a Gaussian term Gfalse(x,yfalse)=expbadbreak−x2+y2w02\begin{align} \text{G}(x,y)=\exp \left(-\frac{x^2+y^2}{w_0^2}\right) \end{align}and a vortex term Vfalse(x,yfalse)=[]false(xxvfalse)+ifalse(yyvfalse)w0l\begin{align} \text{V}(x,y)={\left[\frac{(x-x_v)+\text{i}(y-y_v)}{w_0}\right]}^l \end{align}where w 0 is the initial beam width, l is the topological charge, false(xv,yvfalse)$(x_v,y_v)$ are the coordinates of the vortex, to obtain ESPGVBs, [ 11,13 ] which can be expressed as ESPGVB(x,y)=Pexb1w0,p1Peyb2w0,p2×expbadbreak−x2+y2w02[]false(xxvfalse)+ifalse(yyvfalse)w0l\begin{align} \nonumber \operatorname{ESPGVB}(x,y)=&\operatorname{Pe}{\left(\frac{x}{b...…”
Section: Theory Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…[12]. Let us apply an inverse Fourier transform to it, then we add a Gaussian term Gfalse(x,yfalse)=expbadbreak−x2+y2w02\begin{align} \text{G}(x,y)=\exp \left(-\frac{x^2+y^2}{w_0^2}\right) \end{align}and a vortex term Vfalse(x,yfalse)=[]false(xxvfalse)+ifalse(yyvfalse)w0l\begin{align} \text{V}(x,y)={\left[\frac{(x-x_v)+\text{i}(y-y_v)}{w_0}\right]}^l \end{align}where w 0 is the initial beam width, l is the topological charge, false(xv,yvfalse)$(x_v,y_v)$ are the coordinates of the vortex, to obtain ESPGVBs, [ 11,13 ] which can be expressed as ESPGVB(x,y)=Pexb1w0,p1Peyb2w0,p2×expbadbreak−x2+y2w02[]false(xxvfalse)+ifalse(yyvfalse)w0l\begin{align} \nonumber \operatorname{ESPGVB}(x,y)=&\operatorname{Pe}{\left(\frac{x}{b...…”
Section: Theory Modelmentioning
confidence: 99%
“…where w 0 is the initial beam width, l is the topological charge, (x v , y v ) are the coordinates of the vortex, to obtain ESPGVBs, [11,13] which can be expressed as ESPGVB(x, y) = Pe ] l (3) where Pe( ⋅ ) is the Pearcey function, b 1 , p 1 and b 2 , p 2 are the distribution factors along x and y axes, respectively.…”
Section: Propagation Of Espgvbs In Free Spacementioning
confidence: 99%
“…[1] Since it was first proposed DOI: 10.1002/andp.202100479 in 1946, its generation, control and application have been intensively investigated. [2][3][4][5][6] With the unique properties of inversion, auto-focusing and self-healing, the theoretical introduction and experimental realization in optics, [7] Pearcey beams have attracted widespread attention in recent years, leading to different types of Pearcey beams generation such as dual Pearcey beams, [8] ring and symmetric Pearcey Gaussian (PG) beams [9,10] and partially coherent PG beams. [11] Especially, by imposing Gaussian truncation on ideal Pearcey beams, the physical realization of PG beams with finite energy becomes possible because ideal Pearcey beams have infinite energy.…”
Section: Introductionmentioning
confidence: 99%
“…In 2012, Ring et al theoretically confirmed that the Pearcey function is a particular solution of wave equation under paraxial approximation and successfully generated the Pearcey beams experimentally. [25] In 2014, a virtual source to generate Pearcey beams was demonstrated by Deng et al [26] In 2015, Kovalev et al [27] generated and introduced a family of form-invariant half-Pearcey beams (HP-beams). In 2016, it was reported that, based on the Fresnel diffraction catastrophes, dual Pearcey beams (DP beams) were successfully obtained by interfering a pair of half DP beams, [28] and the form-invariant Bessel beams were experimentally confirmed as particular forms of DP beams.…”
Section: Introductionmentioning
confidence: 99%